Pengukuran Efisiensi Perusahaan Go-Public Sektor Pertanian dan Perkebunan di Indonesia dengan Metode Data Envelopment Analysis (DEA) Bootstrap - Wardoni, Ilham; Wijayanti, Irene Kartika Eka (Universitas Galuh, 2024)
Companies are required to achieve full efficiency, which use of certain inputs to produce optimal output. Efficiency is one of the indicators in measuring the operational performance of a company. This research uses the Bootstrap Data Envelopment Analysis (DEA). The results DMUs full efficiency are BISI, WAPO, LSIP, MGRO and SMAR. Average efficiency of all DMUs is 0.7314 and the priority improvement is DMU BTEK with OFI value of 16.11%. DMUs are Increasing are AALI, ANDI, ANJT, BTEK, BWPT, CSRA, GZCO, JAWA, PGUN and PSGO. DMUs are constant are BISI, WAPO, LSIP, MGRO and SMAR. DMU decreasing is DSNG, FAPA, SGRO, SIMP and SSMS. The highest DEA Bootstrap bias estimate is 0.36 from DMUs full efficiency values. Meanwhile, the lowest bias value is 0.002 from DMU BWPT. The bias estimate between the CCR and Bootstrap DEA models has a difference of 0.199. The DMU becomes a role model and more dominant than other benchmarking peers is SMAR.